Stable bipolarons in open quantum systems - Moroder, Mattia; Grundner, Martin; Damanet, François; Schollwöck, Ulrich; Mardazad, Sam; Flannigan, Stuart; Köhler, Thomas; Paeckel, Sebastian (Physical Review B 107, 214310 (2023))
Recent advances in numerical methods significantly pushed forward the understanding of electrons coupled to quantized lattice vibrations. At this stage, it becomes increasingly important to also account for the effects of physically inevitable environments. In particular, we study the transport properties of the Hubbard-Holstein Hamiltonian that models a large class of materials characterized by strong electron-phonon coupling, in contact with a dissipative environment. Even in the one-dimensional and isolated case, simulating the quantum dynamics of such a system with high accuracy is very challenging due to the infinite dimensionality of the phononic Hilbert spaces. For this reason, the effects of dissipation on the conductance properties of such systems have not been investigated systematically so far. We combine the non-Markovian hierarchy of pure states method and the Markovian quantum jumps method with the newly introduced projected purified density-matrix renormalization group, creating powerful tensor-network methods for dissipative quantum many-body systems. Investigating their numerical properties, we find a significant speedup up to a factor $\sim 30$ compared to conventional tensor-network techniques. We apply these methods to study dissipative quenches, aiming for an in-depth understanding of the formation, stability, and quasi-particle properties of bipolarons. Surprisingly, our results show that in the metallic phase dissipation localizes the bipolarons, which is reminiscent of an indirect quantum Zeno effect. However, the bipolaronic binding energy remains mainly unaffected, even in the presence of strong dissipation, exhibiting remarkable bipolaron stability. These findings shed light on the problem of designing real materials exhibiting phonon-mediated high-$T_C$ superconductivity.

Statistical analysis of initial state and final state response in heavy-ion collisions - Borghini, Nicolas; Borrell, Marc; Feld, Nina; Roch, Hendrik; Schlichting, Sören; Werthmann, Clemens (Phys. Rev. C 107 (2023) 034905)
We develop a general decomposition of an ensemble of initial density profiles in terms of an average state and a basis of modes that represent the event-by-event fluctuations of the initial state. The basis is determined such that the probability distributions of the amplitudes of different modes are uncorrelated. Based on this decomposition, we quantify the different types and probabilities of event-by-event fluctuations in Glauber and Saturation models and investigate how the various modes affect different characteristics of the initial state. We perform simulations of the dynamical evolution with KoMPoST and MUSIC to investigate the impact of the modes on final-state observables and their correlations.

Plant mitochondrial RNA editing factors can perform targeted C-to-U editing of nuclear transcripts in human cells - Lesch, Elena; Schilling, Maximilian T; Brenner, Sarah; Yang, Yingying; Gruss, Oliver J; Knoop, Volker; Schallenberg-Rüdinger, Mareike (Nucleic Acids Research)
Abstract RNA editing processes are strikingly different in animals and plants. Up to thousands of specific cytidines are converted into uridines in plant chloroplasts and mitochondria whereas up to millions of adenosines are converted into inosines in animal nucleo-cytosolic RNAs. It is unknown whether these two different RNA editing machineries are mutually incompatible. RNA-binding pentatricopeptide repeat (PPR) proteins are the key factors of plant organelle cytidine-to-uridine RNA editing. The complete absence of PPR mediated editing of cytosolic RNAs might be due to a yet unknown barrier that prevents its activity in the cytosol. Here, we transferred two plant mitochondrial PPR-type editing factors into human cell lines to explore whether they could operate in the nucleo-cytosolic environment. PPR56 and PPR65 not only faithfully edited their native, co-transcribed targets but also different sets of off-targets in the human background transcriptome. More than 900 of such off-targets with editing efficiencies up to 91%, largely explained by known PPR-RNA binding properties, were identified for PPR56. Engineering two crucial amino acid positions in its PPR array led to predictable shifts in target recognition. We conclude that plant PPR editing factors can operate in the entirely different genetic environment of the human nucleo-cytosol and can be intentionally re-engineered towards new targets.
Keywords: Genetics

Das Hubble-Teleskop: Mehr als 30 Jahre Beobachtung. - Hohmann, Sascha (Astronomie + Raumfahrt im Unterricht)

Comparison: Stochastics with a Focus on Probability Theory - Stoffels, Gero; Hohmann, Sascha (Comparison of Mathematics and Physics Education II. Examples of Interdisciplinary Teaching at School)

Comparison: Equations in Mathematics and Physics Education - Hohmann, Sascha; Pielsticker, Felicitas (Comparison of Mathematics and Physics Education II. Examples of Interdisciplinary Teaching at School)

Das Stellarium Gornergrat: Ein ferngesteuertes Observatorium für Bildungszwecke. - Gschwind, Stéphane; Hohmann, Sascha; Müller, Andreas; Riesen, Timm-Emanuel (Astronomie + Raumfahrt im Unterricht)

Wie die Wikinger das Nordmeer überqueren konnten - Hohmann, Sascha (Astronomie + Raumfahrt im Unterricht)

Wortkritik als Aufgabenfeld einer diversitätssensiblen Literaturdidaktik. Das Verfahren der Dechiffrierung als ein Weg fachintegrativer Verankerung von Diversitätssensibilität - Kißling, Magdalena (Diversitätsorientierte Deutschdidaktik: Theoretisch-konzeptionelle Fundierung und Perspektiven für empirisches Arbeiten. Band 4 SLLD (B))
Keywords: Diversität; Inklusion; Gender; Deutschdidaktik

‚Nofretete-Mädchen‘ als Aufstörende des Adipositas-Mythos. Interkulturelle Perspektive auf Adoleszenz am Beispiel von Stefanie Höflers Tanz der Tiefseequalle - Kißling, Magdalena (Adoleszenz und Alterität. Synergien aktueller Ansätze der interkulturellen Literaturwissenschaft und -didaktik)

Postkolonialismus. Der Deutschunterricht (5) LXXIV

Politik&Co. Wirtschaft-Politik 9/10, Gymnasium Nordrhein-Westfalen - Dieckmann, Eva; Kißling, Magdalena; Labusch, Alexandra; Lindner, Nora; Mertens, Julia; Rohde, Marius

Eine kulinarische Geschlechterordnung? Die Polarisierung von Geschlecht im Kontext medialer Inszenierung und alltagsweltlicher Darstellungen des Kulinarischen - Eremin, Oxana (GENDER. Zeitschrift für Geschlecht, Kultur und Gesellschaft)

#FeministKitchen [Notes] - Eremin, Oxana (FKW//Zeitschrift für Geschlechterforschung und visuelle Kultur)

(K)Eine Frage des Wissens: Zum Verhältnis von Gender Studies & Wissenstransfer - Eremin, Oxana; Krämer, Anike; Mattei, Annalisa (Wissenstransfer als Aufgabe, Herausforderung und Chance kulturwissenschaftlicher Forschung.)

Foodwork: Schlaglichter auf das Themenfeld von Essen, Kochen und Geschlecht - Eremin, Oxana (Soziale Passagen. Journal für Empirie und Theorie Sozialer Arbeit)

Effects of strong fringing magnetic fields on turbulent thermal convection - Bhattacharya, Shashwat; Boeck, Thomas; Krasnov, Dmitry; Schumacher, Jörg (arXiv:2211.00559)
We study the influence of fringing magnetic fields on turbulent thermal convection in a horizontally extended rectangular domain. The magnetic field is created in the gap between two semi-infinite planar magnetic poles, with the convection layer located near the edge of the gap. We employ direct numerical simulations in this setup for fixed Rayleigh and small Prandtl numbers, but vary the fringe-width by controlling the gap between the magnetic poles and the convection cell. The magnetic field generated by the magnets is strong enough to cease the flow in high magnetic flux region of the convection cell. We observe that as the local vertical magnetic field strength increases, the large scale structures become thinner and align themselves perpendicular to the longitudinal sidewalls. We determine the local Nusselt and Reynolds numbers as functions of the local Hartmann number (based on the vertical component of the magnetic field) and estimate the global heat and momentum transport. We show that the global heat transport decreases with increasing fringe-width for strong magnetic fields but increases with increasing fringe-width for weak magnetic fields. In the regions of large vertical magnetic fields, the convective motion becomes confined to the vicinity of the sidewalls. The amplitudes of these wall modes show a non-monotonic dependence on the fringe-width.

VALIDATION AND COMPARISON OF FEM-SIMULATION RESULTS OF THE FUSED DEPOSITION MODELING PROCESS UNDER CONSIDERATION OF DIFFERENT MESH RESOLUTIONS - Moritzer, Elmar; Hecker, Felix (Proceedings of the 33rd Annual Freeform Fabrication Symposium)

New York als Material - Künstlerische Forschung im Spannungsfeld von Kunstgeschichte, Kunstpraxis und Vermittlung - Autsch, Sabiene (Kunstpädagogik und ... Bezugsfelder und Perspektiven kunstpädagogischer Theorie und Praxis)

Die ASK und ihre Ausstellungen. Ein Visual Essay - Autsch, Sabiene; Pickartz, Tim (Bis hierhin und weiter. Hundert Jahre Arbeitsgemeinschaft Siegerländer Künstlerinnen und Künstler [= Publikation anlässlich der gleichnamigen Ausstellung, Städtische Galerie Haus See, Siegen, 29. Mai - 03. Juli 2022])